Disruption of estrogen receptor signaling enhances intestinal neoplasia in Apc(Min/+) mice - Cleveland, Alicia G. (Oxford University Press, 2009)
Estrogen receptors (ERs) [ERα (Esr1) and ERβ (Esr2)] are expressed in the human colon, but during the multistep process of colorectal carcinogenesis, expression of both ERα and ERβ is lost, suggesting that loss of ER function might promote colorectal carcinogenesis. Through crosses between an ERα knockout and Apc(Min) mouse strains, we demonstrate that ERα deficiency is associated with a significant increase in intestinal tumor multiplicity, size and burden in Apc(Min/+) mice. Within the normal intestinal epithelium of Apc(Min/+) mice, ERα deficiency is associated with an accumulation of nuclear β-catenin, an indicator of activation of the Wnt–β-catenin-signaling pathway, which is known to play a critical role in intestinal cancers. Consistent with the hypothesis that ERα deficiency is associated with activation of Wnt–β-catenin signaling, ERα deficiency in the intestinal epithelium of Apc(Min/+) mice also correlated with increased expression of Wnt–β-catenin target genes. Through crosses between an ERβ knockout and Apc(Min) mouse strains, we observed some evidence that ERβ deficiency is associated with an increased incidence of colon tumors in Apc(Min/+) mice. This effect of ERβ deficiency does not involve modulation of Wnt–β-catenin signaling. Our studies suggest that ERα and ERβ signaling modulate colorectal carcinogenesis, and ERα does so, at least in part, by regulating the activity of the Wnt–β-catenin pathway.